Chapter 2 Big stories and small stories in the psychological relief work after the earthquake disaster Life and Death - Kawai, Toshio (Taylor & Francis, 2019)
"This edited book focuses on the organization and meaning of craft work in contemporary society. It considers the relationship between craft and place and how this enables the construction of a meaningful relationship with objects of production and consumption. The book explores the significance of raw materials, the relationship between the body, the crafted object and the mind, and the importance of skill, knowledge and learning in the making process. Through this, it raises important questions about the role of craft in facing future challenges by challenging the logic of globalized production and consumption. The Organization of Craft Work encompasses international analyses from the United States, France, Italy, Australia, Canada, the UK and Japan involving a diverse range of sectors, including brewing, food and wine production, clothing and shoe making, and perfumery. The book will be of interest to students and academic researchers in organization studies, marketing and consumer behaviour, business ethics, entrepreneurship, sociology of work, human resource management, cultural studies, geography, and fashion and design. In addition, the book will be of interest to practitioners and organizations with an interest in the development and promotion of craft work."